THE RELEVANCE OF THE EDUCATIONAL CONCEPT OF KI HAJAR DEWANTARA TO THE MERDEKA CURRICULUM - Wafa, Ali (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The progress of the world of education today cannot be separated from the role of figures as the main actors. A figure who has made a major contribution to the advancement of education in Indonesia and earned the title of Father of National Education, namely Ki. Hajar Dewantara, This research is a library research using a content analysis approach. Educational thinking Ki. Hajar Dewantara is relevant to the independent curriculum which is freedom of thought and freedom of innovation. such as learning objectives, which are equally directing educational goals in four dimensions, namely physical, intellectual, spiritual and social goals. Educational goals namely; equally direct educational goals with regard to the individual and society, the role of the educator . according to Ki. Hajar Dewantara as a facilitator and motivator. Meanwhile, according to the independent curriculum, the role of educators is also as a facilitator in learning and as a learning partner for students. Both agreed that there are four competencies that an educator must have, namely pedagogic, personality, social and professional. The learning principles in the independent curriculum are relevant to the learning principles according to Ki. Hajar Dewantara, namely: the principle of independence, the principle of nationality, the principle of culture, the principle of natural nature, the principle of humanity. Furthermore, regarding learning materials, both agree that learning materials are taught according to the developmental level of the age of students.